Parkin inhibits proliferation and migration of bladder cancer via ubiquitinating Catalase - Renjie Zhang; Wenyu Jiang; Gang Wang; Yi Zhang; Wei Liu; Mingxing Li; Jingtian Yu; Xin Yan; Fenfang Zhou; Wenzhi Du; Kaiyu Qian; Yu Xiao; et al. (Communications Biology, 2024)
Abstract PRKN is a key gene involved in mitophagy in Parkinson’s disease. However, recent studies have demonstrated that it also plays a role in the development and metastasis of several types of cancers, both in a mitophagy-dependent and mitophagy-independent manner. Despite this, the potential effects and underlying mechanisms of Parkin on bladder cancer (BLCA) remain unknown. Therefore, in this study, we investigated the expression of Parkin in various BLCA cohorts derived from human. Here we show that PRKN expression was low and that PRKN acts as a tumor suppressor by inhibiting the proliferation and migration of BLCA cells in a mitophagy-independent manner. We further identified Catalase as a binding partner and substrate of Parkin, which is an important antioxidant enzyme that regulates intracellular ROS levels during cancer progression. Our data showed that knockdown of CAT led to increased intracellular ROS levels, which suppressed cell proliferation and migration. Conversely, upregulation of Catalase decreased intracellular ROS levels, promoting cell growth and migration. Importantly, we found that Parkin upregulation partially restored these effects. Moreover, we discovered that USP30, a known Parkin substrate, could deubiquitinate and stabilize Catalase. Overall, our study reveals a novel function of Parkin and identifies a potential therapeutic target in BLCA.